Comparative Study of Stress Between Engineering and Medical Students - Patel, Sonam; A.K. , Agrawal (International Journal of Psychosocial Rehabilitation, 2020)
An attempt has been made to study the comparison of stress between engineering and medical students of the Bundelkhand area of Uttar Pradesh. For this purpose, the ‘Students’ Stress Scale’ by Dr. Taresh Bhatia & Arunima Pathak was administered to 200 engineering and 200 medical students of the Bundelkhand region selected through a stratified random sampling technique. The mean, standard deviation, and critical ratio were calculated. The results showed that the medical students have significantly higher stress than engineering students at the 0.01 level. The medical students have significantly higher academic, financial, vocational, family, emotional, and social stress than engineering students.